Construction of the readiness attitude scale facing socio-natural disasters - Quispe Leiva, Rossana Marilia (2018)
The purpose of this research was the Scale of Attitudes for Preparedness in the Face of Social Disasters in the population of the San Diego de Alcalá Association in the district of San Martín de Porres, whose line of research is psychometric. A pilot test consisting of 80 participants of the same association was carried out, in order to validate the instrument, after which the scale was applied to the general sample, which were 350 inhabitants of the selected association. The research design is experimental, Instrumental and exploratory level. The main objective is to design the scale and find its psychometric properties. Content validity was carried out through the review of 20 expert judges in psychology; the process of construct validity was carried out by means of the correlation of the articles - test and items - factor. With respect to the reliability of the test, a value of .888 was obtained, according to the Cronbach’s Alpha method; Likewise in the analysis of reliability by means of the method of separation of the cities, the score of .877 was achieved reaffirming the existing reliability. To complete the investigation, the general scoring categories and by each factor were carried out according to the sex of the participants and concluded that the test is valid and reliable.